2020
DOI: 10.1016/j.joule.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Efficiency of Engineered Electromicrobial Production

Abstract: We have developed a theory that lets us calculate the efficiency of microbes that absorb electricity and store CO 2 as biofuels with greater efficiency than photosynthesis. We outline 10 development scenarios including re-engineering direct electron uptake microbes with high-efficiency CO 2 fixation; scaling up H 2oxidizing microbe systems to store megawatts of electricity; engineering direct electron uptake microbes to make highly conductive artificial biofilms to enable high power density electricity storage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(145 citation statements)
references
References 158 publications
5
125
0
Order By: Relevance
“…Their study also indicates that gas recycling to increase overall CO 2 utilization will be necessary when scaling-up these systems. Salimijazi et al (2020) also very recently developed a mathematical model to determine the maximum theoretical efficiency of MES processes from electrical power to biofuels. They predicted that by using highly engineered microorganisms, the conversion efficiency to biofuels could increase up to 52%.…”
Section: Introductionmentioning
confidence: 99%
“…Their study also indicates that gas recycling to increase overall CO 2 utilization will be necessary when scaling-up these systems. Salimijazi et al (2020) also very recently developed a mathematical model to determine the maximum theoretical efficiency of MES processes from electrical power to biofuels. They predicted that by using highly engineered microorganisms, the conversion efficiency to biofuels could increase up to 52%.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, PMES system could be an attractive solution, which provides us an opportunity to drive green fuels from CO 2 at a competitive price. Recently, Salimijazi et al., nicely analyzed the engineering constraints of MES and provided the model-based solutions, reaching at least 50% electrical to biofuel conversion efficiency in PMES ( Salimijazi et al., 2020 ). However, this process needs substantial development before its application in real condition.…”
Section: Outlook and Future Prospectivementioning
confidence: 99%
“…Already, the Bionic Leaf device has demonstrated that technologies of this class could dramatically exceed the efficiency of photosynthesis 7,8 . However, while highly efficient at lab scale, the Bionic Leaf relies on H2-oxidation to transfer electrons from the electrode to microbes, and the low solubility of H2 in water would pose a significant challenge for scale-up of this and related technologies 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring electroactive microbes can produce acetate and butyrate from CO2 and electricity with Faradaic efficiencies exceeding 90% 16 . Furthermore, theoretical analysis suggests that the upper limit efficiency of electromicrobial production of biofuels by EEU could rival that of H2-mediated systems 9 . However, naturally occurring electroactive organisms capable of EEU suffer from multiple technical drawbacks.…”
Section: Introductionmentioning
confidence: 99%